A polyfluoroalkyl amino active silicone oil
Patent Information
- Application Number
- CN202611142960.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-09-11
AI Technical Summary
[0005]本发明旨在解决调控本征不相容链段的空间拓扑结构以实现匀相热力学亚稳定储存并在非饱和缩聚固化中协同达成低表面能与高界面锚定耐久性的问题
1、在多氟烷基氨基活性硅油中,通过限定多氟烷基氨基活性聚硅氧烷基料中活性氨基与氟原子的摩尔比值在特定区间,使氨基的局域亲水偶极矩与多氟烷基的疏水排斥力在链段尺度达成动力学平衡,并结合侧链聚醚改性烷氧基封端聚硅氧烷相容剂的聚醚侧链段通过氢键网络作用环绕于多氟烷基氨基活性聚硅氧烷基料的氨基外部,在异构烷烃反应介质中构建出规整的胶束阻障,抑制多氟烷基链段的自发性聚集与局域相分离,使组合物在不借助外部小分子表面活性剂的前提下维持稳定的储存热力学亚稳定状态,避免传统体系中因外加助剂向表面迁移富集而屏蔽氟碳链段低表面能防护特性的技术缺陷。
Smart Images

Figure CN122726697A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer protective materials technology, and particularly relates to a polyfluoroalkyl amino active silicone oil. Background Technology
[0002] Currently, the use of polysiloxane compositions containing side-chain polyfluoroalkyl units and active amino units as protective coatings is a common choice. This material relies on the flexibility of the polysiloxane skeleton to achieve surface coverage, and forms chemical bonds between the active amino units in the side chains and the substrate surface. The polyfluoroalkyl groups provide hydrophobic and oleophobic defense properties. The homogeneous stability of the modified polymer depends on the thermodynamic compatibility between the units. The side-chain polyfluoroalkyl units have low polarizability and strong exclusivity, while the active amino units have strong dipole moments. The parameter differences and steric hindrance between the two lead to inherent thermodynamic properties of mutual repulsion between functional chain segments.
[0003] Under the pressure of continuous shear flow fields or long-term high-temperature alternating storage, the inherent thermodynamic properties induce nonlinear phase region aggregation and stratification. The system is prone to phase separation at the chain segment spatial scale and loss of homogeneity. To control such incompatibility of internal chains, surfactants are usually introduced to construct micelles or strong polar cosolvents are added. However, these methods often lead to network reconstruction imbalance. Simply increasing the cosolvent or simply increasing the length of fluorocarbon units not only fails to maintain the stability of the composition but also reduces the protective efficacy of the film. This approach, which relies on external additives, cannot simultaneously ensure the compactness of the film and the durable adhesion of the interface under the premise of stable storage. Conventional modification is limited not only in the formulation compounding morphology that relies on external additives but also in the in-situ control of chain segment incompatibility through the resin skeleton structure. There are also shortcomings in process control. For example, Chinese invention patent application CN1395601A discloses a room temperature curing coating composition. The prior art constructs a low VOC resin system by in-situ polymerization of functional olefin unsaturated monomers in polysiloxane reactive diluents. It belongs to the overall resin blending or conventional free radical interpenetrating network control. When faced with the complex working conditions of strong exclusive low surface energy fluorocarbon units and high dipole moment polar units coexisting, it lacks precise dynamic balance control of intrinsic thermodynamic repulsion forces at the chain segment scale. It cannot spontaneously construct regular micelle barriers to inhibit phase separation. Moreover, it cannot drive the side chains and main chains to undergo substrate orientation pinning and air interface orientation rearrangement when moisture triggers polycondensation. The film-forming product is still prone to local peeling of the coating and accelerated degradation of protective performance due to the aggregation of internal topological voids or surface phase regions.
[0004] Therefore, the technical problem to be solved by this invention is how to achieve stable thermodynamic metastable storage in a homogeneous polycondensation system without added surfactants by controlling the spatial balance between the main polymer chain configuration and the functional parameters of the side chains, and synergistically improve the low surface energy defense characteristics of the air interface and the durable anchoring ability of the substrate interface of the cured film. Summary of the Invention
[0005] This invention aims to solve the problem of controlling the spatial topology of intrinsically incompatible segments to achieve homogeneous thermodynamic metastable storage and synergistically achieving low surface energy and high interfacial anchoring durability in unsaturated polycondensation curing.
[0006] In this technical solution, a polyfluoroalkylamino active silicone oil comprises: The mixture comprises, by weight, 18.5% to 28.0% of a side-chain polyether-modified alkoxy-terminated polysiloxane compatibilizer; 2.5% to 5.5% of a complexed organotitanate crosslinking and curing modifier; 10.0% to 18.0% of an isoparaffinic reaction medium; and a polyfluoroalkylamino-active polysiloxane material to be made up to 100% balance; wherein the molar ratio of active amino to fluorine atoms in the polyfluoroalkylamino-active polysiloxane material is 0.42 to 0.58; The molecular weight distribution index of the side-chain polyether modified alkoxy-terminated polysiloxane compatibilizer is 1.18 to 1.26; The polyfluoroalkyl amino-active polysiloxane material contains polyfluoroalkyl side chains and aminoalkyl main chains. The side-chain polyether modified alkoxy-terminated polysiloxane compatibilizer is formed by the condensation of ethylene oxide segments, propylene oxide segments, and dimethylsiloxane segments, and its molecular chain ends have alkoxy functional groups. The complexed organic titanate crosslinking curing regulator contains titanate chelates combined with tertiary monocarboxylic acids. Under the condition of absorbing environmental moisture and removing isomeric alkane reaction media, the alkoxy functional groups at the end of the side-chain polyether modified alkoxy-terminated polysiloxane compatibilizer dehydrate and condense with the main chain of the polyfluoroalkyl amino-active polysiloxane material.
[0007] Preferably, it also includes a sterically hindered aliphatic monocarboxylic acid, with a mass percentage of 0.8% to 1.6%; the sterically hindered aliphatic monocarboxylic acid forms a coordination complex structure with a complexed organotitanate crosslinking curing regulator; the polyfluoroalkyl amino active silicone oil forms a cured film layer with a three-dimensional crosslinked network structure after absorbing environmental moisture and removing isoparaffin reaction medium, wherein the amino backbone in the polyfluoroalkyl amino active polysiloxane material is distributed on the substrate surface and forms a contact surface, and the polyfluoroalkyl side chains in the polyfluoroalkyl amino active polysiloxane material are distributed on the air interface away from the substrate surface.
[0008] Preferably, the polyfluoroalkyl side chain in the polyfluoroalkyl amino-active polysiloxane material is a fluorocarbon side chain containing 3 to 8 carbon atoms; the aminoalkyl main chain in the polyfluoroalkyl amino-active polysiloxane material has an aminopropyl functional group or an aminoethylaminopropyl functional group.
[0009] Preferably, the polyether-modified side chain in the side-chain polyether-modified alkoxy-terminated polysiloxane compatibilizer is formed by block copolymerization of ethylene oxide segments and propylene oxide segments, wherein the molar ratio of ethylene oxide segments to propylene oxide segments is 1:1 to 3:1.
[0010] Preferably, the complexed organic titanate crosslinking curing modifier is selected from organic titanium chelates of tetraisopropyl titanate or tetrabutyl titanate.
[0011] Preferably, the isoalkane reaction medium is composed of cyclopentamethoxysiloxane and isoalkane solvent mixed in a 1:1 mass ratio.
[0012] Preferably, the sterically hindered aliphatic monocarboxylic acid is selected from 2-ethylhexanoic acid or neodecanoic acid.
[0013] Preferably, its solid content is 82.0% to 90.0%, and its dynamic viscosity at 25°C is 50 mPa·s to 500 mPa·s.
[0014] Preferably, the cured film is formed under conditions of ambient humidity of 50% to 70% and temperature of 20°C to 25°C, and the surface of the cured film has a static contact angle with water greater than or equal to 110° and a static contact angle with hexadecane greater than or equal to 70°.
[0015] Compared with the prior art, the polyfluoroalkyl amino active silicone oil of the present invention has the following advantages: 1. In polyfluoroalkyl amino active silicone oil, by limiting the molar ratio of active amino to fluorine atoms in polyfluoroalkyl amino active polysiloxane material within a specific range, the local hydrophilic dipole moment of the amino group and the hydrophobic repulsion force of the polyfluoroalkyl group achieve a kinetic equilibrium at the chain segment scale. Combined with the polyether side segments of the side-chain polyether modified alkoxy-terminated polysiloxane compatibilizer, which surround the amino group of polyfluoroalkyl amino active polysiloxane material through hydrogen bonding network, a regular micelle barrier is constructed in the isoalkane reaction medium, which inhibits the spontaneous aggregation and local phase separation of polyfluoroalkyl segments. This allows the composition to maintain a stable thermodynamic metastable state without the aid of external small molecule surfactants, avoiding the technical defect of traditional systems where the low surface energy protection properties of fluorocarbon segments are shielded due to the migration and enrichment of added additives to the surface.
[0016] 2. Relying on environmental moisture to trigger the in-situ generation of silanol units from the terminal siloxane units in the side-chain polyether-modified alkoxy-terminated polysiloxane compatibilizer, and driven by the catalysis of the complexed organic titanate crosslinking curing regulator, the units undergo dehydration condensation reaction with the main chain active sites in the polyfluoroalkyl amino active polysiloxane material. Accompanied by the removal of chelating ligands by the complexed titanium crosslinking agent, it participates in the coordination crosslinking of molecular chain segments to form a three-dimensional network with high crosslinking density. This curing film formation method based on the condensation of uncarbon-carbon unsaturated bonds does not require the assistance of strong polar organic co-solvents, and blocks the formation of internal surface pinhole defects during volatilization and removal, so that the film product has a dense overall topological structure. Combined with interface durability pinning, it eliminates the local peeling of the coating and the accelerated degradation of protective performance caused by defect stress concentration under complex working conditions.
[0017] 3. In the cross-linking, curing, shrinkage, and rearrangement of the network structure, the active amino functional groups in the polyfluoroalkyl amino-active polysiloxane material migrate toward the surface of the high surface energy inorganic or metal substrate, and are tightly locked at the substrate interface through electrostatic attraction and hydrogen bonding. At the same time, under the compression of the cross-linking network shrinkage and rearrangement, the polyfluoroalkyl segments are oriented toward the air interface away from the substrate, and a high-density self-healing fluorine low surface energy defense layer emerges in situ at the interface. This not only gives the cured film layer stable substrate adhesion and shear fluid erosion resistance, but also preserves the intrinsic low surface energy protection effect, avoiding the conflict between low surface energy and high adhesion in traditional fluorosilicone protective materials. Attached Figure Description
[0018] Figure 1 This is a flowchart of the unsaturated polycondensation curing and interface arrangement of polyfluoroalkyl amino active silicone oil according to the present invention. Figure 2 This is a structural diagram showing the composition and proportioning parameters of the polyfluoroalkyl amino active silicone oil components of the present invention. Figure 3 This is the large framework structure diagram of the chemical molecular formula of the polyfluoroalkyl amino active silicone oil of the present invention. Detailed Implementation
[0019] The technical solutions of the embodiments of this application will be clearly described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this application are within the scope of protection of this application.
[0020] A polyfluoroalkyl amino active silicone oil, comprising: The mixture comprises, by weight, 18.5% to 28.0% of a side-chain polyether-modified alkoxy-terminated polysiloxane compatibilizer; 2.5% to 5.5% of a complexed organotitanate crosslinking and curing modifier; 10.0% to 18.0% of an isoparaffinic reaction medium; and a polyfluoroalkylamino-active polysiloxane material to be made up to 100% balance; wherein the molar ratio of active amino to fluorine atoms in the polyfluoroalkylamino-active polysiloxane material is 0.42 to 0.58; The molecular weight distribution index of the side-chain polyether modified alkoxy-terminated polysiloxane compatibilizer is 1.18 to 1.26; The polyfluoroalkyl amino-active polysiloxane material contains polyfluoroalkyl side chains and aminoalkyl main chains. The side-chain polyether modified alkoxy-terminated polysiloxane compatibilizer is formed by the condensation of ethylene oxide segments, propylene oxide segments, and dimethylsiloxane segments, and its molecular chain ends have alkoxy functional groups. The complexed organic titanate crosslinking curing regulator contains titanate chelates combined with tertiary monocarboxylic acids. Under the condition of absorbing environmental moisture and removing isomeric alkane reaction media, the alkoxy functional groups at the end of the side-chain polyether modified alkoxy-terminated polysiloxane compatibilizer dehydrate and condense with the main chain of the polyfluoroalkyl amino-active polysiloxane material.
[0021] Preferably, it also includes a sterically hindered aliphatic monocarboxylic acid, with a mass percentage of 0.8% to 1.6%; the sterically hindered aliphatic monocarboxylic acid forms a coordination complex structure with a complexed organotitanate crosslinking curing regulator; the polyfluoroalkyl amino active silicone oil forms a cured film layer with a three-dimensional crosslinked network structure after absorbing environmental moisture and removing isoparaffin reaction medium, wherein the amino backbone in the polyfluoroalkyl amino active polysiloxane material is distributed on the substrate surface and forms a contact surface, and the polyfluoroalkyl side chains in the polyfluoroalkyl amino active polysiloxane material are distributed on the air interface away from the substrate surface.
[0022] Preferably, the polyfluoroalkyl side chain in the polyfluoroalkyl amino-active polysiloxane material is a fluorocarbon side chain containing 3 to 8 carbon atoms; the aminoalkyl main chain in the polyfluoroalkyl amino-active polysiloxane material has an aminopropyl functional group or an aminoethylaminopropyl functional group.
[0023] Preferably, the polyether-modified side chain in the side-chain polyether-modified alkoxy-terminated polysiloxane compatibilizer is formed by block copolymerization of ethylene oxide segments and propylene oxide segments, wherein the molar ratio of ethylene oxide segments to propylene oxide segments is 1:1 to 3:1.
[0024] Preferably, the complexed organic titanate crosslinking curing modifier is selected from organic titanium chelates of tetraisopropyl titanate or tetrabutyl titanate.
[0025] Preferably, the isoalkane reaction medium is composed of cyclopentamethoxysiloxane and isoalkane solvent mixed in a 1:1 mass ratio.
[0026] Preferably, the sterically hindered aliphatic monocarboxylic acid is selected from 2-ethylhexanoic acid or neodecanoic acid.
[0027] Preferably, its solid content is 82.0% to 90.0%, and its dynamic viscosity at 25°C is 50 mPa·s to 500 mPa·s.
[0028] Preferably, the cured film is formed under conditions of ambient humidity of 50% to 70% and temperature of 20°C to 25°C, and the surface of the cured film has a static contact angle with water greater than or equal to 110° and a static contact angle with hexadecane greater than or equal to 70°.
[0029] Example 1: In the application scenario of metal pipeline protection that needs to withstand continuous high-speed fluid scouring and intermittent high temperature and high humidity alternating storage, polymer protective coatings face stability defects such as polar chain segment delamination and local phase separation. Due to the strong exclusivity of polyfluoroalkyl side chains and the strong dipole moment of active amino backbone chains, there is thermodynamic mutual repulsion between the two in terms of molecular chain segment arrangement. In the process of condensation curing film formation based on reactions other than carbon-carbon unsaturated bonds, traditional external additives tend to spontaneously migrate and accumulate to the surface of resin coating, thus shielding the low surface energy characteristics. Moreover, when the strong polar cosolvent evaporates and is removed, it generates irregular topological voids and local pinhole defects in the polymer matrix. This leads to local peeling, cracking and degradation of protective layer performance.
[0030] To address the aforementioned operating conditions, the local kinetic barrier mechanism of the components of a polyfluoroalkylamino active silicone oil during the mixing, dispersion, and static storage stages is as follows: A 13.0% by mass isoparaffinic reaction medium, composed of cyclopentamethoxydimethylsiloxane and isoparaffinic solvent mixed in a 1:1 mass ratio, is injected into a sealed reactor. The shear rate of the stirring system is controlled at 1350 rpm, and the system temperature is kept constant at 35°C. A 58.0% by mass polyfluoroalkylamino active polysiloxane material, with a molar ratio of active amino to fluorine atoms of 0.45, is added in batches. The high-shear flow field, combined with the isotropic medium, prevents intramolecular fluorine entanglement. To generate a homogeneous diluted phase, the polyfluoroalkylamino active polysiloxane material is a colorless to pale yellow transparent liquid with a number average molecular weight of 4500 g / mol to 6500 g / mol. The main chain is copolymerized from dimethylsiloxane and aminopropylmethylsiloxane segments, and the side chain contains trifluoropropyl fluorocarbon side chains. During the synthesis stage, a co-hydrolysis condensation reaction is carried out by precisely controlling the molar ratio of dichlorodimethylsilane, dichloromethylaminopropylsilane, and polyfluoroalkylmethyldichlorosilane. After the reaction, low molecular weight cyclic impurities with a molecular weight below 500 g / mol are removed by a high-temperature vacuum distillation process. This precisely locks the molar ratio of active amino to fluorine atoms to 0.45 at the polymer reaction source. The reaction is carried out under stirring at a constant temperature of 1... A 24.0% (w / w) side-chain polyether-modified alkoxy-terminated polysiloxane compatibilizer was added at a dropping rate of 0.8 kg / min. This compatibilizer has a molecular weight distribution index (MDI) of 1.22 and is composed of ethylene oxide, propylene oxide, and dimethylsiloxane segments, with alkoxy functional groups at the ends of the molecular chains. The molar ratio of ethylene oxide to propylene oxide segments is 2:1. To overcome the inherent wide molecular weight distribution defect of the condensation reaction and achieve a narrow orientation distribution of 1.22, the compatibilizer, after undergoing the dehydration condensation reaction of the ethylene oxide, propylene oxide, and dimethylsiloxane segments, is directly introduced into a precision cascade thin-film evaporator and supercritical carbon dioxide fluid fractionation purification process. The chemical system, under equilibrium conditions of stable vacuum of 5 Pa and operating temperature of 180℃, performs continuous countercurrent extraction and separation to precisely remove high molecular weight easily gelling components and low molecular weight oligomer free bodies. After three repeated cascade fractionation operations, the ratio of heavy average molecular weight to number average molecular weight is forced to converge within an extremely narrow closed-loop range of 1.18 to 1.26. Under mass transfer kinetics, the polyether side chains of the side-chain polyether modified alkoxy-terminated polysiloxane compatibilizer surround the amino group of the polyfluoroalkyl amino active polysiloxane material through hydrogen bonding network to construct a spatially regular micelle barrier, inhibiting the spontaneous aggregation of polyfluoroalkyl chain segments. Under light-protected conditions, the shear rate is reduced to 400 rpm and 4% by mass is added.0% of a complexed organic titanate crosslinking and curing regulator selected from tetraisopropyl titanate organotitanium chelates. The pre-preparation process of the aforementioned complexed organic titanate crosslinking and curing regulator before its introduction into the system is as follows: Tetraisopropyl titanate and neodecanoic acid are introduced together in a 1:2 molar ratio into a sealed pre-reaction vessel equipped with a reflux condenser and a vacuum filtration device. The mechanical shear speed of the stirring system is controlled at 200 rpm, the reaction temperature is kept constant at 80°C, and the chemical reaction is continued for 3 hours under a nitrogen atmosphere with a purity greater than 99.9%. By in-situ substitution of a portion of the isopropoxy group on tetraisopropyl titanate with the tertiary monocarboxylic acid group of neodecanoic acid, the byproduct isopropanol produced in the reaction is completely removed from the system by vacuum distillation at 60°C, thereby obtaining a stable tertiary monocarboxylic acid-modified titanate chelate, and 1.0% by mass of a sterically hindered aliphatic monocarboxylic acid selected from 2-ethylhexanoic acid. The sterically hindered aliphatic monocarboxylic acid forms a coordination complex structure with a complexing organic titanate crosslinking and curing regulator, and simultaneously reacts with a polyfluoroalkylamino active polysiloxane via proton transfer. In situ, free amino groups in the base material construct a thermo-regulated, dynamically reversible ammonium salt network. The high polarity of the ammonium salt alters the local solubility parameters of the system, suppressing the tendency for low-temperature self-aggregation and crystallization of fluorocarbon segments. This maintains a stable thermodynamic metastable state for storage without the aid of external small-molecule surfactants. The aforementioned thermo-regulated, dynamically reversible ammonium salt network exhibits a clear temperature response boundary: under storage conditions below 15°C, the carboxyl protons of sterically hindered aliphatic monocarboxylic acids spontaneously and completely transfer to the active amino groups, constructing a highly polar transient ammonium salt associative network in situ. By significantly altering the system's local solubility parameters to completely passivate and shield the dipole moment of free amino groups, hydrolysis and gelation induced by trace amounts of moisture are physically blocked. When the system temperature rises back to the operational window of 20°C to 35°C, the ammonium salt network undergoes dynamic dissociation driven by thermodynamics, with protons undergoing reverse proton transfer and smoothly releasing free active amino groups. The entire thermally induced dissociation and state transition process includes a 5-minute transition equilibrium blind zone delay period, during which the system's kinematic viscosity fluctuates by less than 5%, ensuring a safe and stable transition from the stored state to the solidified crosslinked state.
[0031] When polyfluoroalkyl amino active silicone oil is applied to the inner wall surface of a metal pipe, its unsaturated condensation curing film formation and interface adaptive arrangement mechanism are as follows: Under the conditions of 60% humidity and 22℃, the complexed organic titanate crosslinking curing regulator absorbs ambient moisture and removes isomeric alkane reaction media, causing the alkoxy functional groups at the end of the side-chain polyether modified alkoxy-terminated polysiloxane compatibilizer to generate silanol units in situ. Under the catalytic drive of the crosslinking curing regulator, these units undergo dehydration condensation with the main chain of the polyfluoroalkyl amino active polysiloxane material. Accompanied by the removal of chelating ligands from the complexed titanium, these units participate in molecular chain segment coordination crosslinking to form a spatial crosslinked network structure. During the crosslinking, curing, shrinkage, and rearrangement process of the network structure, the polyfluoroalkyl amino... The amino backbone of the polysiloxane-based active polysiloxane material has an aminopropyl functional group, which migrates toward the surface of the high surface energy metal substrate and is tightly locked to the substrate surface through electrostatic attraction and hydrogen bonding to form a contact surface. At the same time, the polyfluoroalkyl amino active polysiloxane material contains 6 carbon atoms of polyfluoroalkyl side chain, which is oriented toward the air interface away from the substrate surface under the compression of cross-linking network contraction and rearrangement. This blocks the formation of internal pinhole defects during volatilization and removal, so that the cured film layer exhibits a dense overall topological structure. Its surface has a static contact angle of water greater than or equal to 110° and a static contact angle of hexadecane greater than or equal to 70°, maintaining a stable protective life under continuous fluid erosion and evolution conditions.
[0032] Example 2: When a polyfluoroalkylamino active silicone oil system faces shearing conditions within a pipeline caused by high-speed fluid flow, a coating fluid shear flow monitoring device is used to provide flow stress constraints in order to determine the anti-shear delamination performance of the protective film layer during the conformational evolution of local molecular chain segments. This device includes a high-precision fluid shear regulation vessel in a sealed chamber and an online fiber Raman spectroscopy measurement circuit. The mechanical stirring shaft of the high-precision fluid shear regulation vessel generates a shear speed range of 0 to 2500 rpm within the sealed chamber, with an internal temperature variation of less than or equal to 0.1℃. It outputs flow friction data via a shear stress sensing unit fixed to the inner wall of the reactor chamber. The shear stress sensing unit has a reading resolution of 0.01 Pa and a signal acquisition sampling frequency greater than or equal to 1000 Hz, providing feedback on the rheological flow state of the silicone oil. The online fiber Raman spectroscopy measurement circuit has a spectral line resolution of 1 cm⁻¹. -1This study utilizes an insertable sapphire fiber optic probe to penetrate the coated liquid film and obtain local scattering band changes of the fluorocarbon side chains and amino backbone. In the data integration control of the measurement loop, the determination of the integration time width of the Raman scattering signal from the spectral probe is constrained by the transient changes in liquid film thickness caused by fluid flow field fluctuations and the thermal effect of laser irradiation. It requires balancing the signal-to-noise ratio of spectral absorbance characteristics with the real-time capture of local phase region coarsening. If the integration time width is greater than the conventional relaxation time, the inflection point signal of structural abrupt changes caused by high-speed scouring will overlap in the time domain. If the integration time width is less than the detection limit, insufficient photon count will cause intrinsic scattering noise to submerge the molecular fingerprint peaks. The control rule is determined by the product of the rate of change of the stirring shaft's rotational shear stress and the rearrangement barrier of the polysiloxane molecular chain segments. When the product of the rate of change and the rearrangement barrier increases, the integration time width is crucial for capturing the local phase region sliding characteristics before unsaturated polycondensation crosslinking. The adjustment is directed towards the lower limit of its set range. Specifically, the aforementioned adjustment process relies on a pre-set digital imaging program to reduce and normalize the overall mechanical parameters and surface molecular barriers. The program calibrates the rate of change of rotational shear stress collected by the shear stress sensing unit in real time using Pascals per second as the unit, and converts the polysiloxane molecular chain rearrangement barrier into an equivalent kilojoule / molar scalar value based on the thermodynamic activation energy. When the product of the rate of change of rotational shear stress and the scalar value of rearrangement barrier increases by 1000 engineering units, the control program issues a hardware trigger command to monotonically decrease the sampling integration time width of the online fiber Raman spectroscopy measurement loop by 2 milliseconds. This imaging program limits the closed-loop working dead zone range from 10 milliseconds to 100 milliseconds, thereby eliminating the dimensional mismatch between mechanical quantities and molecular timing, and achieving accurate capture of cross-scale transition states, corresponding to a scouring flow velocity of 5 m / s and a local shear rate of 1200 s. -1Under fluid flow conditions, the Raman scattering signal integration time width was adjusted to 10 ms to obtain data on the localized aggregation state of molecules. To verify the proportion boundaries of each active component in the condensation polymer raw material and the function of each functional group in the unsaturated bond-free condensation reaction, multiple reaction samples with clearly defined material ratios were prepared. Sample group one of this invention contains 58.0% by mass of polyfluoroalkyl amino-active polysiloxane material, wherein the molar ratio of aminopropyl active amino to six-carbon fluorine side chain fluorine atoms is 0.45, and 24.0% by mass of side chain polyether-modified alkoxy-terminated polysiloxane compatibilizer with a weight average molecular weight to number average molecular weight ratio of 1.22, and it contains ethylene oxide segments and propylene oxide segments. The invention also includes a dimethylsiloxane segment, wherein the molar ratio of ethylene oxide to propylene oxide is 2:1, and the main chain ends with isopropoxy-terminated functional groups; a crosslinking curing regulator selected from tetraisopropyl titanate at a mass percentage of 4.0%; an isoalkane reaction medium composed of cyclopentamethoxydimethylsiloxane and higher isoalkane in a 1:1 mass ratio at a mass percentage of 13.0%; and a sterically hindered aliphatic monocarboxylic acid selected from 2-ethylhexanoic acid at a mass percentage of 1.0%. Sample group two of the invention is used to define the lower limit of the material ratio and includes a polyfluoroalkylamino active polysiloxane material at a mass percentage of 68.0%, wherein the molar ratio of active amino to fluorine atoms is 0.42, and the mass percentage is 18.5%. The present invention comprises: a side-chain polyether-modified alkoxy-terminated polysiloxane compatibilizer with a weight-to-number molecular weight ratio of 1.18; a crosslinking and curing regulator of 2.5% by mass; and an isoparaffinic reaction medium of 11.0% by mass. Sample group three of the present invention, used to limit the upper limit of the material ratio, comprises: a polyfluoroalkylamino active polysiloxane material of 52.5% by mass, wherein the molar ratio of active amino to fluorine atoms is 0.58; a side-chain polyether-modified alkoxy-terminated polysiloxane compatibilizer of 28.0% by mass, with a weight-to-number molecular weight ratio of 1.26; a crosslinking and curing regulator of 5.5% by mass; and an isoparaffinic reaction medium of 14.0% by mass. The reaction medium consists of % isoparaffins; Partially missing control group one is used to block the steric isolation effect of the compatibilizer, comprising 72.0% by mass of polyfluoroalkylamino active polysiloxane material, 4.0% by mass of crosslinking curing regulator, 23.0% by mass of isoparaffins, and 1.0% by mass of sterically hindered aliphatic monocarboxylic acid; Partially missing control group two is used to block the transient protective effect of monocarboxylic acid, comprising 59.0% by mass of polyfluoroalkylamino active polysiloxane material, 24.0% by mass of side-chain polyether modified alkoxy-terminated polysiloxane compatibilizer, 4.0% by mass of crosslinking curing regulator, and 13% by mass of...0% isoparaffinic reaction medium; Out-of-range control group one deviates from the lower end of the compatibilizer range and contains 67.0% by mass of polyfluoroalkylamino active polysiloxane material, 15.0% by mass of side-chain polyether modified alkoxy-terminated polysiloxane compatibilizer, 4.0% by mass of crosslinking curing regulator, 13.0% by mass of isoparaffinic reaction medium, and 1.0% by mass of sterically hindered aliphatic monocarboxylic acid; Out-of-range control group two deviates from the upper end of the compatibilizer range and contains 50.0% by mass of polyfluoroalkylamino active polysiloxane material, 32.0% by mass of side-chain polyether modified alkoxy-terminated polysiloxane compatibilizer, 4.0% by mass of crosslinking curing regulator, 13.0% by mass of isoparaffinic reaction medium, and 1.0% by mass of sterically hindered aliphatic monocarboxylic acid.
[0033] Each of the above samples was sealed and stored in a constant temperature and humidity environment chamber with a temperature variation of less than or equal to 0.5℃ and a relative humidity of 60%. After a static storage period of 30 days to provide thermodynamic aging load, the mechanical stirring shaft speed was kept constant at 1350 rpm to apply a continuous shear flow stress field. The two-phase aggregation phase change of polymer molecules inside the coating liquid film was tracked using an online fiber Raman spectroscopy measurement loop. The detection data showed that sample group 1, sample group 2, and sample group 3 of the present invention all maintained a stable single homogeneous liquid physical property state during the static storage and continuous shear flow stress field processes. Among them, the characteristic scattering peak position of the polar amino functional group and the polyoxyethylene unit of the polyether side chain of sample group 1 of the present invention was stable at 2932 cm⁻¹. -1At this location, the scattering spectrum peak showed no discrete broadening at half maximum width, indicating that under the dynamics of spatial mass transfer concentration gradient, the polyether segments of the side-chain polyether-modified alkoxy-terminated polysiloxane compatibilizer are coated around the hydrophilic aminopropyl backbone of the polyfluoroalkyl amino-active polysiloxane material through intermolecular hydrogen bonding, forming a micelle barrier and blocking the spontaneous localized crystalline phase aggregation of the low surface energy polyfluoroalkyl side chains. In contrast, the partially missing control group showed nonlinear peak splitting and liquid film turbidity and stratification in its Raman fingerprint scattering characteristic peak after 4.2 minutes of operation in the shear flow field. This phenomenon is caused by the lack of spatial micelle barrier between the polar repulsive backbone and the strongly exclusive fluorocarbon segments due to the absence of compatibilizer components, thus inducing spontaneous coarsening of the anisotropic phase region. The crystallization is the cause. Simultaneously, the partially missing control group II, after 15.2 days of static storage, showed a change in kinematic viscosity from the initial 152 mPa·s to 4580 mPa·s, indicating a loss of gel flowability and a deterioration inflection point. This phenomenon is due to the lack of sterically hindered aliphatic monocarboxylic acids, preventing the free amino groups from forming a dynamic reversible ammonium salt network. This results in a loss of the ability to inhibit residual trace moisture within the cavity, triggering a localized intermolecular condensation reaction of silanols catalyzed by the crosslinking curing regulator. The out-of-range control group I, due to the compatibilizer mass percentage being below the lower limit of 18.5%, could not form a completely covering steric micelle barrier around the polar backbone. Under flow shear, the polyfluoroalkyl side chains underwent localized phase aggregation and reached 2965 cm⁻¹. -1 The peaks showing aggregation and crystallization splitting are present in the control group 2, which is outside the range. Although the compatibilizer mass percentage is higher than the upper limit of 28.0%, it maintains a homogeneous state in the liquid storage stage, but in the subsequent cross-linked film layer, it produces water absorption and swelling structural deformation defects due to the excessive introduction of flexible hydrophilic polyether segments.
[0034] The reactants, after undergoing storage aging and continuous flow shearing, were sprayed onto the inner surface of the steel pipe. The temperature of the curing reaction chamber was controlled at 22°C and the relative humidity was maintained at 60%. The crosslinking curing regulator in the material reacted by absorbing moisture from the air and removing isoparaffin reaction media. The isopropoxy functional group at the end of the compatibilizer was converted into a silanol backbone, which catalyzed the dehydration and polycondensation of the silanol backbone with the polyfluoroalkyl amino-active polysiloxane backbone. Accompanied by the removal of chelating ligands by the complexed titanium, it formed a coordination network crosslink with the co-condensed polymer backbone. During the spontaneous shrinkage and compaction of the network structure, the hydrophilic aminopropyl backbone of the base material migrated toward the high surface energy of the steel inner surface and was tightly locked in contact by electrostatic attraction and hydrogen bonds. The fluorocarbon side chains containing six carbon atoms are oriented and densely packed towards the air interface away from the inner surface of the steel under the force of molecular chain compression and rearrangement. Under this film-forming process, the protective coating generated by the condensation polymerization of the sample group of this invention has an average thickness of 45.3 μm. When faced with a low scouring load of 2 m / s fluid velocity and 50% relative humidity, its static water contact angle is measured to be 113.1° and its hexadecane contact angle is 73.2°. After a continuous scouring process of 150 h, its interfacial adhesion retention rate is 97.4%. When faced with a medium scouring load of 5 m / s fluid velocity and 60% relative humidity, its static water contact angle is measured to be 112.4° and its hexadecane contact angle is 72.1°. After a scouring process of 150 h, its interfacial adhesion retention rate is 97.4%. After 150 hours, the interfacial adhesion retention rate was 95.6%. Under the dual loads of high scouring and high humidity (fluid velocity 12 m / s and relative humidity 85%), the static water contact angle remained stable at 110.5°, and the hexadecane contact angle remained stable at 70.2°. After 150 hours of scouring, the interfacial adhesion retention rate remained at 88.3%. The physical parameters showed a monotonically converging trend of scouring resistance variation with increasing load intensity, without any phase region peeling or fracture characteristics. Under the same moderate scouring load environment, the average thickness of the protective coating generated by the dicondensation of the sample group of this invention was 43.1 μm, with a static water contact angle of 110.2° and a hexadecane contact angle of 70.3°. After 150 hours of scouring, the adhesion retention rate remained stable at 95.6%. The adhesion retention rate was 91.2%. The average thickness of the protective coating generated by the tricondensation of the sample group of this invention was 47.8 μm, with a static water contact angle of 114.1° and a hexadecane contact angle of 73.5°. After 150 h of rinsing, the adhesion retention rate was 93.4%. In contrast, under the same moderate rinsing load, due to pinhole cavity defects caused by phase separation, the thickness of the partially missing control group after curing was randomly and roughly distributed between 12.5 μm and 85.2 μm. Its initial static water contact angle degraded to 84.6° and the hexadecane contact angle degraded to 41.5°. After 11.3 h of fluid rinsing operation, the entire protective layer blistered and peeled off from the metal substrate, with an adhesion retention rate of less than 15%.The initial adhesion of the coating was 0%, while the partially missing control group 2, due to its failure to build a protective network during storage, underwent slow hydrolysis and gelation prematurely, resulting in lower initial adhesion. After 50.4 hours of fluid flushing, the protective layer experienced local delamination and fracture, and the adhesion retention rate decreased to 47.5%. The out-of-range control group 1 had an initial static water contact angle of 91.8° after curing, but after 30.5 hours of fluid flushing, the static water contact angle abruptly dropped to 76.2° due to damage to the uniformity of the local molecular layer phase region. The out-of-range control group 2 experienced adhesion retention rate reduction to 38.4% after 45.2 hours of fluid flushing due to excessive water absorption and swelling of the polyether segment, leading to shear cracking of the network cross-linked skeleton. The data from the entire study confirm that the interfacial peel life of the protective coating on the inner wall of metal pipes constitutes a monotonically determined causal relationship with the spatial regularity of the two-phase distribution of the curing film precursor and the integrity of the titanium ether dehydration polycondensation cross-linked network.
[0035] Example 3: When the polyfluoroalkylamino active silicone oil system is applied to the inner wall protective component of a steel color conveying pipeline in a closed, high-humidity storage environment, due to the permeation and diffusion of trace amounts of ambient moisture into the liquid interior, the system is prone to hydrolysis and alcoholysis of unsaturated polycondensation reaction, leading to localized uneven gelation and loss of fluidity. In order to determine the process control boundary of sterically hindered aliphatic monocarboxylic acid in blocking the pre-hydrolysis catalysis of crosslinking curing regulator, its initial state is limited to a closed reaction chamber with a temperature control error of less than or equal to 0.5°C and an air relative humidity maintained at 75%, with air of a certain mass fraction of moisture introduced as the initial reaction atmosphere. The initial kinematic viscosity of the polyfluoroalkylamino active polysiloxane material, which is the main body of the hydrolysis reaction, is stable in the range of 150 mPa·s to 160 mPa·s, and the molar ratio of active amino to fluorine atoms in the base material is locked at the lower protection limit of 0.42. The shear mixing speed of the high-precision reactor is maintained at 400 rpm to maintain the laminar dispersion state.
[0036] The process for determining and optimizing the working window for the addition of sterically hindered aliphatic monocarboxylic acids is as follows: Five groups of samples with progressively increasing mass percentages were prepared. The mass percentages of the sterically hindered aliphatic monocarboxylic acids were determined to be 0.2%, 0.5%, 1.0%, 2.0%, and 2.5%, respectively. The remaining components maintained a monotonic correspondence, i.e., the mass percentage of the polyfluoroalkylamino reactive polysiloxane alkyl material was monotonically fine-tuned to keep the total component amount constant at 100%. Each group of samples was placed in the initial reaction atmosphere and allowed to stand for 168 hours. The evolution trend of the kinematic viscosity of the system was monitored using an online viscometer, and the diffusion resistance coefficient of the cured film after cross-linking was measured using a dynamic mechanical analyzer. When the mass percentage of the sterically hindered aliphatic monocarboxylic acid was lower than the process lower limit of 0.5%, due to the thermally regulated dynamic equilibrium ammonium salt... The insufficient density of local chemical sites in the network makes it impossible to completely shield the polar dipoles of free amino groups. This leads to a silanol condensation reaction rate induced by trace amounts of moisture exceeding the dynamic ammonium salt equilibrium rate. As a result, the system exhibits localized gelation and precipitation with a kinematic viscosity greater than 10,000 mPa·s by the 48th hour. Furthermore, when the mass percentage of sterically hindered aliphatic monocarboxylic acids exceeds the process upper limit of 2.0%, excessive free acid undergoes over-coordination substitution with the complexed organic titanate crosslinking curing regulator. This results in steric hindrance passivation defects in the active centers of the titanium catalytic catalyst during the curing film formation stage. The dehydration condensation reaction between the polymer backbones is incomplete, leaving unreacted carboxylic acid molecules within the cured layer. Consequently, the dielectric permeation and diffusion coefficient of the cured film under continuous scouring conditions increases to 3.5 times that of the unadded state, leading to a decrease in protective shielding effectiveness.
[0037] Based on the calculation of the nonlinear extreme value overlap range of the viscosity rise rate and the permeation diffusion coefficient, the preferred addition mass percentage of sterically hindered aliphatic monocarboxylic acid converges within a closed working window of 0.5% to 2.0%. Within this preferred range, the local chemical potential and catalytic activation energy of the ammonium salt transient protection network maintain thermodynamic equilibrium. After the sample is left to stand for 168 hours in a closed high-humidity storage environment, the kinematic viscosity only fluctuates slightly from 155 mPa·s to 182 mPa·s. Moreover, the integrity of the unsaturated dehydration polycondensation crosslinking network during curing application remains above 96.5%, and the interfacial adhesion retention rate of the cured film layer in high-speed fluid scouring application scenarios is greater than or equal to 95.0%. This data confirms that sterically hindered aliphatic monocarboxylic acid, together with the active base material and crosslinking regulator, constructs a synergistic barrier within the closed process range, coordinating the technical problem of the conflict between the easy hydrolysis of the active material during high-humidity storage and the high curing crosslinking density during film formation.
[0038] Example 4: In the application of protective coating to the inner wall of steel color conveying pipelines, due to the uneven initial roughness and polar oxide density of the inner wall of different batches of pipe materials, the protective coating is prone to local variations in interface pinning force during curing. Therefore, before large-scale construction, pre-calibration was performed using samples from the same batch. The initial surface free energy of the substrate was measured using a tension tester. The spraying atomization pressure was adjusted to 0.3MPa, 0.4MPa, and 0.5MPa in an enabled environment with a temperature of 22℃ and a relative humidity of 60% to construct a pre-formed film layer with a thickness gradient. After controlling the curing process to reach 24 hours, the adhesion retention rate and fluorocarbon side chain close packing index were measured to obtain the benchmark values of the process control parameters for the current batch of pipe materials. The aforementioned fluorocarbon side chain close packing index was obtained by total reflection Fourier transform infrared spectroscopy. The external spectral detection procedure is used for purely digital characterization. The specific implementation steps are as follows: the film sample cured for 24 hours is placed on the test stage, and a solid pressure bar is used to press the sapphire total internal reflection crystal component tightly against the air interface surface of the cured film. The infrared spectral scanning program is started to obtain the total internal reflection absorbance spectrum. The absolute absorbance values of the carbon-hydrogen bond symmetric stretching vibration absorption peak at 2920 wavenumber and the carbon-fluorine bond stretching vibration absorption peak at 1240 wavenumber are directly extracted from the spectrum. The fluorocarbon side chain close packing index is obtained by calculating the dimensionless ratio of the carbon-fluorine bond absorbance value to the carbon-hydrogen bond absorbance value. When this ratio is within the quantization range of 1.8 to 2.5, it objectively confirms that the polyfluoroalkyl side chains have achieved a high-density oriented close packing topology at the air interface.
[0039] Based on the baseline values of process control parameters, polyfluoroalkyl amino active silicone oil was sprayed onto the inner wall surface of the pipe component. The spraying atomization pressure was locked at 0.42 MPa and the spray gun target distance was kept constant at 250 mm, so that the cured thickness of the protective layer converged to 45.5 μm. In the unsaturated dehydration condensation reaction film rearrangement, the hydrophilic aminopropyl main chain migrated toward the high surface energy substrate and generated a cross-linked anchoring layer, while the fluorocarbon side chains were oriented and densely packed toward the air interface. Measurement data showed that the water contact angle of the cured protective film reached 112.6° and the hexadecane contact angle reached 72.4°. After being subjected to continuous flushing of 12 m / s fluid for 150 h, its adhesion retention rate remained stable at 95.2%, and no local peeling or cracking failure of the coating due to substrate deviation occurred.
[0040] Example 5: When the system faces the condition of non-uniform fluctuations in the initial roughness of the inner wall of different batches of metal pipes and the density of polar oxides, the substrate anchoring durability and storage phase stability of the polymer protective coating become mutually restrictive technical problems. In order to determine the optimal mass percentage of sterically hindered aliphatic monocarboxylic acid as the protective regulating component, the system is configured with a standardized parameter gradient offline calibration process. This offline calibration process prepares five groups of samples with progressively increasing mass percentages. The mass percentage of sterically hindered aliphatic monocarboxylic acid in each sample is set to 0.5%, 0.8%, 1.2%, 1.6%, and 2.0% respectively. The mass percentage of polyfluoroalkylamino reactive polysiloxane alkyl material is adjusted accordingly to keep the sum of the mass percentages of each component constant at 100%. Each group of samples is placed in a reaction chamber with a controlled temperature of 50°C and a relative humidity of 75% to apply a hydrothermal aging load.
[0041] The kinematic viscosity evolution of each sample over time was monitored using an online viscometer, and the diffusion resistance coefficient of the cured film after crosslinking was tested using a dynamic mechanical analyzer. The data showed that when the mass percentage of sterically hindered aliphatic monocarboxylic acids was less than 0.8%, due to insufficient local chemical site density in the ammonium salt transient protective network, the free amino groups could not be shielded at the chain segment scale polar dipoles. The rate of silanol polycondensation induced by trace amounts of moisture exceeded the dynamic ammonium salt equilibrium rate. As a result, the system exhibited localized gelation with a kinematic viscosity greater than 10000 mPa·s after 48 hours of standing, accompanied by increased fluidity. When the mass percentage of sterically hindered aliphatic monocarboxylic acids exceeds 1.6%, the excess free acid undergoes excessive coordination substitution with the complexed organic titanate crosslinking curing regulator, leading to steric passivation of the active titanium catalytic center during the curing film formation stage. The hydrolysis and condensation reaction between the main chain of the polyfluoroalkyl amino active polysiloxane material and the terminal silanoxy group of the side-chain polyether modified alkoxy-terminated polysiloxane compatibilizer is incomplete, resulting in the arrangement of unreacted carboxylic acid small molecules inside the cured layer. This causes the dielectric permeation and diffusion coefficient of the cured film to increase to 3.5 times that of the unadded state under continuous scouring conditions, resulting in a decrease in the protective shielding effectiveness.
[0042] When the mass percentage of sterically hindered aliphatic monocarboxylic acids is between 0.8% and 1.6%, the kinematic viscosity of the sample fluctuates only from 155 mPa·s to 182 mPa·s after standing for 168 h, and the integrity of the unsaturated dehydration polycondensation crosslinking network during curing application remains above 96.5%. When the sample prepared within this working window is sprayed onto the inner wall of a metal pipe, under curing conditions of 60% humidity and 22℃, the hydrophilic aminopropyl backbone migrates toward the metal substrate surface and generates a crosslinked anchoring layer, while the fluorocarbon side chains are oriented and densely packed toward the air interface. The static water contact angle of the protective film reaches 112.6°, and the static contact angle of hexadecane reaches 72.4°. After being subjected to continuous flushing with 12 m / s fluid for 150 h, its adhesion retention rate remains at 95.2%.
[0043] Example 6: To verify the hair repair and interfacial charge regulation performance of the polyfluoroalkyl amino active silicone oil of the present invention in personal care and advanced hair care products, this example, based on a specific molecular structure framework, introduces a high dipole moment silicon-oxygen structural unit in situ into its polyfluoroalkyl amino active polysiloxane material. The local units in the microstructure framework of this base material satisfy the following: the central silicon atom is bonded to R1, R2, and R3 groups respectively through three oxygen atoms, and the fourth bond position of the silicon atom is connected to the active amino group (-NH2) through an amino-containing alkyl chain; the topological parameters of each substituent group are finely controlled to cover a wide range of structural boundaries. R1 and R2 groups are selected as perfluoroalkyl groups, with a carbon number of 6. The remaining R3 group is selected as an alkoxy chain, specifically a butoxy group. The amino-containing side chain has an alkyl chain length of 3 carbon atoms, which is aminopropyl. In the formulation of the hair conditioner lotion, the polyfluoroalkyl amino active silicone oil composition prepared in the specified proportion is used as a functional additive. It is uniformly dispersed at a mass percentage of 2.5% in a composite emulsion fluid medium composed of fatty alcohol polyoxyethylene ether, hexadecyltrimethylammonium chloride, and deionized water. The mixture is stirred using a mechanical stirring system at a shear rate of 1200 rpm and a temperature of [missing information]. High-speed shear dispersion at 40°C, thanks to the orderly arrangement of fluorocarbon side chains under the spatial mass transfer concentration gradient, resulted in a homogeneous stability of up to 60 days without the addition of additional traditional small-molecule surfactants. No localized spontaneous phase aggregation or nonlinear stratification was observed. When this conditioning emulsion containing polyfluoroalkyl amino active silicone oil was applied to the surface of damaged human hair fibers, the localized damage to the polar protein structure on the surface of the hair fibers led to the widespread exposure of negatively charged potential microregions. The aminopropylamino (-NH2) in the silicone oil molecule of this invention exhibited good stability in an aqueous environment. The active amino units in the molecule can spontaneously protonate and acquire a strong positive charge. Driven by a strong local dipole moment and electrostatic attraction, the positively charged active amino units migrate toward the negatively charged surface of the damaged hair strand. They are tightly pinned and locked to the substrate surface through electrostatic attraction and hydrogen bonding, achieving a precise fixation and repair effect. The two perfluoroalkyl groups provided by R1 and R2 in the molecular framework, with 6 carbon atoms, spontaneously orient themselves toward the air interface away from the hair substrate surface under the kinetic compression of liquid film drying and network contraction and rearrangement. The fluorocarbon side chain close packing index of the air interface surface layer reached 2 as determined by total reflectance Fourier transform infrared spectroscopy.15. A high-density, self-healing fluorine-based low surface energy defense layer emerges at the interface. Tests show that the static contact angle of the treated hair surface with water monotonically increases from 52° in the original damaged state to 108°, significantly reducing tear and moisture evaporation in the ocular and hair environments. Simultaneously, due to the extremely low surface coverage steric hindrance and excellent smoothing properties provided by the fluorosilicone polymer smooth skeleton, the hair is endowed with an ultra-soft, smooth, and fluffy feel. After undergoing 30 consecutive standard shampoo washes, the silicone oil retention rate on the hair surface remains as high as 89.4%, demonstrating adhesion durability and wash resistance that are difficult for conventional fluorosilicone materials to match.
[0044] Example 7: To further verify the industrial technical performance of the polyfluoroalkyl amino active silicone oil of the present invention as the king of softeners, endowing fabrics with ultimate softness, smoothness, fluffy feel, and ultra-high durability and wash resistance in the textile finishing field, a large framework structure that greatly broadens the chain length of perfluoroalkyl and ordinary alkyl groups was used for compounding and pad-dyeing tests. In this large molecular framework, as the microscopic skeleton unit of the polyfluoroalkyl amino active polysiloxane material, among the R1, R2, and R3 groups connected by the central silicon atom, only one R1 group is selected as a long-chain perfluoroalkyl group, and the number of carbon atoms of the perfluoroalkyl group is set to 12. This is used to regulate a more extreme low surface energy hydrophobic and oleophobic defense boundary; the remaining R2 and R3 groups are selected as conventional aliphatic alkoxy functional groups, with a corresponding chain length of 8 carbon atoms (octyloxy); the amino-containing side chain has a chain length of 6 carbon atoms (aminohexyl); this polyfluoroalkyl amino-active polysiloxane material with a specific long-chain topological network and satisfying a large framework configuration is used as the core material, and is mixed with 20.0% by mass of side-chain polyether modified alkoxy-terminated polysiloxane compatibilizer, 4.0% complexed organotitanate crosslinking curing regulator, and 16% by mass of polyether modified alkoxy-terminated polysiloxane compatibilizer, 4.0% complexed organotitanate crosslinking curing regulator, and 16% by mass of polyether modified alkoxy-terminated polysiloxane compatibilizer, octyl ...0% isoalkane reaction medium was rapidly mixed; the temperature was controlled at 35℃ in a closed reactor, and the stirring shear rate was maintained at 1350 rpm, so that the components could construct a well-organized micelle barrier in the isoalkane medium, successfully maintaining a stable thermodynamic metastable storage state without the addition of small molecule surfactants. This active silicone oil composition was applied to the surface of a high-density pure cotton fabric fiber substrate by padding process. During the film-forming and curing process at an ambient humidity of 65% and a temperature of 25℃, complexed organic titanate... The cross-linking curing regulator absorbs environmental moisture and removes isomeric alkane reaction media, triggering an in-situ unsaturated dehydration condensation reaction. This drives intense co-condensation between the alkoxy groups at the end of the compatibilizer and the main chain of the active silicone oil base material. Under the dynamic compression of this three-dimensional network cross-linking shrinkage rearrangement, the amino-containing side chains with a chain length of 6 carbon atoms exhibit highly polar intrinsic dipoles, oriented towards the surface of the high surface energy cellulose inorganic fiber substrate. The amino units undergo strong electrostatic attraction and microscopic topological chemical reactions with polar hydroxyl groups and other groups on the fiber surface, forming a... A durable, robust, and highly elastic soft film tightly locks in and forms the contact surface. Simultaneously, the extra-long perfluoroalkyl R1 side chains containing 12 carbon atoms, driven by the spontaneous contraction and compaction of the cross-linked backbone, undergo high-density oriented packing towards the air interface away from the fabric substrate, spontaneously emerging in situ a high-density, low-surface-energy protective layer. Measurement data show that the cured fabric film surface exhibits a static contact angle of 115° with water and 74° with hexadecane, demonstrating extremely excellent hydrophobic and oleophobic properties. Dual protective properties; due to the topological synergistic effect of the extra-long chain fluorocarbon units and the highly flexible siloxane backbone, the treated fabric achieves an extremely smooth, delicate, fluffy, and full ultra-soft touch. When the fabric was placed in a standard industrial washing machine for accelerated wash resistance tumbling tests, after undergoing 50 consecutive standard cycles of high-intensity washing, the static water contact angle on the fabric surface remained stable at 111°, with an interfacial adhesion and soft hand feel retention rate as high as 91.5%, and no local peeling, cracking, or deterioration of the protective phase layer were observed.
[0045] The embodiments of this application have been described above with reference to the accompanying drawings. Unless otherwise specified, the embodiments and features in the embodiments of this application can be combined with each other. This application is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many other forms under the guidance of this application without departing from the spirit of this application and the scope of protection of this invention, and all of these forms are within the protection scope of this application.
Claims
1. A polyfluoroalkyl amino active silicone oil, characterized in that, include: The mixture comprises, by weight, 18.5% to 28.0% of a side-chain polyether-modified alkoxy-terminated polysiloxane compatibilizer; 2.5% to 5.5% of a complexed organotitanate crosslinking and curing modifier; 10.0% to 18.0% of an isoparaffinic reaction medium; and a polyfluoroalkylamino-active polysiloxane material to be made up to 100% balance; wherein the molar ratio of active amino to fluorine atoms in the polyfluoroalkylamino-active polysiloxane material is 0.42 to 0.58; The molecular weight distribution index of the side-chain polyether modified alkoxy-terminated polysiloxane compatibilizer is 1.18 to 1.26; The polyfluoroalkyl amino-active polysiloxane material contains polyfluoroalkyl side chains and aminoalkyl main chains. The side-chain polyether modified alkoxy-terminated polysiloxane compatibilizer is formed by the condensation of ethylene oxide segments, propylene oxide segments, and dimethylsiloxane segments, and its molecular chain ends have alkoxy functional groups. The complexed organic titanate crosslinking curing regulator contains titanate chelates combined with tertiary monocarboxylic acids. Under the condition of absorbing environmental moisture and removing isomeric alkane reaction media, the alkoxy functional groups at the end of the side-chain polyether modified alkoxy-terminated polysiloxane compatibilizer dehydrate and condense with the main chain of the polyfluoroalkyl amino-active polysiloxane material.
2. The polyfluoroalkylamino active silicone oil according to claim 1, characterized in that, It also includes sterically hindered aliphatic monocarboxylic acids, with a mass percentage of 0.8% to 1.6%; the sterically hindered aliphatic monocarboxylic acids and complexed organotitanate crosslinking curing modifier form a coordination complex structure; the polyfluoroalkyl amino active silicone oil forms a cured film layer with a three-dimensional crosslinked network structure after absorbing environmental moisture and removing isoparaffin reaction medium, wherein the amino backbone of the polyfluoroalkyl amino active polysiloxane material is distributed on the substrate surface and forms a contact surface, and the polyfluoroalkyl side chains of the polyfluoroalkyl amino active polysiloxane material are distributed on the air interface away from the substrate surface.
3. The polyfluoroalkylamino active silicone oil according to claim 1, characterized in that, The polyfluoroalkyl side chains in polyfluoroalkyl amino-active polysiloxane materials are fluorocarbon side chains containing 3 to 8 carbon atoms; the aminoalkyl backbone in polyfluoroalkyl amino-active polysiloxane materials has an aminopropyl functional group or an aminoethylaminopropyl functional group.
4. The polyfluoroalkylamino active silicone oil according to claim 1, characterized in that, The polyether-modified side chains in the side-chain polyether-modified alkoxy-terminated polysiloxane compatibilizer are formed by block copolymerization of ethylene oxide segments and propylene oxide segments, wherein the molar ratio of ethylene oxide segments to propylene oxide segments is 1:1 to 3:
1.
5. The polyfluoroalkylamino active silicone oil according to claim 1, characterized in that, The complexed organic titanate crosslinking and curing modifier is selected from organic titanium chelates of tetraisopropyl titanate or tetrabutyl titanate.
6. The polyfluoroalkylamino active silicone oil according to claim 1, characterized in that, The isoparaffin reaction medium is composed of cyclopentamethoxysiloxane and isoparaffin solvent mixed in a 1:1 mass ratio.
7. The polyfluoroalkylamino active silicone oil according to claim 2, characterized in that, The sterically hindered aliphatic monocarboxylic acids are selected from 2-ethylhexanoic acid or neodecanoic acid.
8. The polyfluoroalkylamino active silicone oil according to claim 1, characterized in that, Its solid content is 82.0% to 90.0%, and its dynamic viscosity at 25°C is 50 mPa·s to 500 mPa·s.
9. The polyfluoroalkylamino active silicone oil according to claim 2, characterized in that, The cured film is formed under conditions of ambient humidity of 50% to 70% and temperature of 20°C to 25°C. The static contact angle of the surface of the cured film with water is greater than or equal to 110° and the static contact angle with hexadecane is greater than or equal to 70°.
Citation Information
Patent Citations
Ambient temp. curing coating composition
CN1395601A